THE INFLUENCE OF FASHION INFLUENCER AND E-COMMERCE ON PURCHASE INTENTION THROUGH BRAND ATTITUDE ON PUTRI AGATA FASHION PRODUCTS IN BIMA (CASE STUDY CONDUCTED IN BIMA CITY) - Nurchairunisyah, Nurchairunisyah; Widodo, Teguh; Dewi, Widi (Universitas Riau Kepulauan, 2025)
This study aims to analyze the influence of fashion influencers and E-Commerce on purchase intention through brand attitude in Putri Agata fashion products in Bima. The research employs a quantitative approach with data processed using SPSS and collected through questionnaires and interviews. Validity tests, reliability tests, F-tests, T-tests, determination tests, and path analysis were utilized to analyze the data.The results show that: (1) Fashion influencers significantly influence brand attitude; (2) E-Commerce significantly influences brand attitude; (3) Brand attitude significantly influences consumers' purchase intention; (4) Fashion influencers directly have a significant impact on consumers' purchase intention; (5) E-Commerce also directly has a significant impact on consumers' purchase intention; (6) The indirect influence of fashion influencers on purchase intention through brand attitude demonstrates a smaller contribution compared to its direct effect; (7) The indirect influence of E-Commerce on purchase intention through brand attitude is also smaller than its direct effect.The analysis confirms that the direct influence of fashion influencers and E-Commerce on purchase intention is more dominant than the indirect pathways through brand attitude. These findings suggest that interventions focusing directly on fashion influencers and E-Commerce variables can have a more effective impact on enhancing consumers' purchase intention.